2017
DOI: 10.1007/s10880-017-9524-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Attitudes Toward Immunosuppressant Therapy in a Multi-ethnic Sample of Kidney Transplant Recipients

Abstract: Barriers for renal transplant patients to immunosuppressant medication adherence are poorly understood, despite the high rate and toll of non-adherence. We sought to assess factors that contribute to barriers to immunosuppressive medication adherence in an ethnically diverse sample of 312 renal transplant patients recruited from three transplant centers across New York City. Transplant patients who were at least 6 months post-transplant completed questionnaires while waiting for their medical appointment. Ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…However, other studies of kidney recipients found adherence was not associated with concerns about immunosuppressants (as measured by the BMQ) 6,26. One possible explanation for the discrepancy is that recipients had different perceptions about immunosuppressants 34. Nonadherent recipients in the present study may have had more concerns about the potential for adverse effects of immunosuppressants compared with adherent recipients.…”
Section: Discussioncontrasting
confidence: 72%
“…However, other studies of kidney recipients found adherence was not associated with concerns about immunosuppressants (as measured by the BMQ) 6,26. One possible explanation for the discrepancy is that recipients had different perceptions about immunosuppressants 34. Nonadherent recipients in the present study may have had more concerns about the potential for adverse effects of immunosuppressants compared with adherent recipients.…”
Section: Discussioncontrasting
confidence: 72%
“…Studies conducted in Juiz de Fora, Brazil, and Pittsburgh, United States, reported that higher income was associated with MNA, whereas a study conducted in New York, United States, reported that lower income was associated with MNA. 33 , 47 , 48 In the United States, 70% of KTRs reported serious problems with paying for their medications, and 68% of KTRs reported deaths or graft losses as a result of cost-related MNA. 49 By contrast, in Japan, patients have free access to any healthcare provider, from small clinics to large hospitals with the latest facilities, and the self-pay burden of KTRs is minimized to only 0 to 20 000 yen according to income level by the country’s Medical Payment for Services and Supports for Persons with Disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of ethnicity, non-Caucasian's adherence type was most likely to be intentional nonadherence (i.e., I refused to take my medication) because they have greater concerns about the effectiveness of the medication[ 39 ]. A similar study by Constantiner et al .,[ 55 ] found that Blacks and Hispanics (non-Caucasians) reported significantly more barriers to consuming immunosuppressant medication than Caucasians. However, there were no apparent differences in controllable barriers (e.g., “I miss a dose of my immunosuppressant medication (s) as I think there may be side effects”) in Constantiner's study.…”
Section: Discussionmentioning
confidence: 99%